Significance of miscibility in multidonor bulk heterojunction solar cells. Issue 2 (25th September 2015) - Hartmeier, Benjamin F.; Brady, Michael A.; Treat, Neil D.; Robb, Maxwell J.; Mates, Thomas E.; Hexemer, Alexander; Wang, Cheng; Hawker, Craig J.; Kramer, Edward J.; Chabinyc, Michael L.
ABSTRACT: Ternary organic blends have potential in realizing efficient bulk heterojunction (BHJ) organic solar cells by harvesting a larger portion of the solar spectrum than binary blends. Several challenging requirements, based on the electronic structure of the components of the ternary blend and their nanoscale morphology, need to be met in order to achieve high power conversion efficiency in ternary BHJs. The properties of a model ternary system comprising two donor polymers, poly(3‐hexylthiophene) (P3HT) and a furan‐containing, diketopyrrolopyrrole‐thiophene low‐bandgap polymer (PDPP2FT), with a fullerene acceptor, PC61 BM, were examined. The relative miscibility of PC61 BM with P3HT and PDPP2FT was examined using diffusion with dynamic secondary ion mass spectrometry (dynamic SIMS) measurements. Grazing incidence small and wide angle X‐ray scattering analysis (GISAXS and GIWAXS) were used to study the morphology of the ternary blends. These measurements, along with optoelectronic characterization of ternary blend solar cells, indicate that the miscibility of the fullerene acceptor and donor polymers is a critical factor in the performance in a ternary cell. A guideline that the miscibility of the fullerene in the two polymers should be matched is proposed and further substantiated by examination of known well‐performing ternary blends. The ternary blending of semiconducting components can improve the power conversion efficiency of bulk heterojunction organic photovoltaics. The blending of P3HT and PDPP2FT with PC61 BM leads to good absorptive coverage of the incident solar spectrum and cascading transport energy levels. The performance of this ternary blend reveals the impact of the miscibility of PC61 BM in each polymer as a function of composition, highlighting an important factor for optimization of ternary BHJs. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2016, 54, 237–246 Abstract : The ternary blending of semiconducting components can improve the power conversion efficiency of bulk heterojunction organic photovoltaics. The blending of P3HT and PDPP2FT with PC61 BM leads to good absorptive coverage of the incident solar spectrum and cascading transport energy levels. The performance of this ternary blend reveals the impact of the miscibility of PC61 BM in each polymer as a function of composition, highlighting an important factor for optimization of ternary BHJs.